Association of Anti-Mullerian Hormone with Some Physiological and immunological Parameters of Infertile Males: AMH, Physioimmunology in Infertile Males - Najim K. Sabir, Fakhir (Cellular and Molecular Biology, 2022)
The measurement of anti-Müllerian hormone (AMH), which is released in the serum and seminal fluid is a specific indicator of Sertoli cell function. This study aimed to evaluate AMH as a potential clinical indicator of infertility in males with normal and low sperm concentrations, as well as those with primary and secondary infertility. It was a retrospective analysis of 140 males chosen from sole infertility and IVF center in Erbil. without a known cause of infertility, 40 men with normal sperm counts, 100 men with primary, and 40 men with secondary infertility were assessed. An in-house ELISA was used to assess the serum AMH. Semen parameters, Semen and sera cytokines, and certain sex hormone mean levels were compared and correlated with AMH as the primary outcome measures. Seminal and serum AMH levels in infertile males were significantly lower. While an insignificant correlation was detected between AMH and LH, prolactin, or testosterone in azoospermic men, there was a significant adverse association between seminal AMH and FSH. A substantial positive association between seminal AMH and testosterone was found in oligospermia men, although no significant correlations were observed with FSH, LH, or prolactin. In conclusion, AMH in seminal plasma is a reliable marker of male infertility with a role in sperm production.